KAPASITAS ADSORPSI SERBUK NATA DE COCO (BACTERIAL SELLULOSE) TERHADAP ION Pb2+ MENGGUNAKAN METODE BATCH - C. A. Saputri (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2020)
The purpose of this research is determine adsorption capacity of nata de coco powder to the ion Pb2+. Nata de coco is a cellulose derived from the fermentation of Acetobacter xylinum bacteria. Nata de coco powder is made by mashed nata de coco then heated at 80oC, mashed and sifted up to 30-40 mesh size. Characterization includes determination of moisture content, ash content, density and amount of iodine adsorbed. Optimum contact time using batch method with time variation are 20, 40, and 60 minutes. The determination of the capacity of adsorption using the isotherm pattern of Langmuir and Freundlich using variation concentrations Pb2+ 15, 30, 45, and 60 ppm. Amount of adsorbed ion Pb2+ measured by using the Atomic Absorption Spectrophotometry (AAS) at a maximum wavelength of Pb2+ that is 283 nm. The results showed that the optimum time was reached at 60 minutes. Adsorption pattern approach to the Freundlich’s Isotherm models with an adsorption capacity 2.34 mg/g. Keywords: adsorption capacity, Freundlich’s isotherm, ion Pb2+, nata de coco powder